Answer :

Given: x = a cos3 θ

y = b sin3 θ

Consider L.H.S. =


= (cos3 θ)2/3 + (sin3 θ)2/3

= (cos2 θ + (sin2 θ)

= 1 = R.H.S.

Hence, proved.

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Related Videos
Trigonometric IdentitiesTrigonometric IdentitiesTrigonometric Identities39 mins
Trigonometric Identities-IITrigonometric Identities-IITrigonometric Identities-II43 mins
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
view all courses